Analysis of Steel Bridge Frame Reinforcement Using External Prestressing Method Due to Moving Loads - Noor, Rusandi; Mustaqim, Muhammad; Mufassirin Liana, Ulwiyah Wahdah; Siregar, Adde Currie (LPPI Universitas Muhammadiyah Kalimantan Timur (UMKT), 2025)
Bridge reinforcement with external prestressing method is a proven effective approach to overcome damage in strengthening bridge structures. This method uses the installation of prestressing cables outside the steel frame of the bridge to increase the strength and stability of the structure. The bridge structure is made with the guidelines of SNI 1725: 2016 standard steel frame of class A bridges, using IWF and H Beam steel, with a plate thickness of 20 mm with a span length of 60 meters, a width of 9.13 meters and a height of 6.3 meters. The structural analysis of this study uses the SAP2000 v22 software program. In this study, 3 prestressing cable tensions were compared on the reinforcement of the bridge frame with the external prestressing method. And a loading simulation was carried out which could provide a response in the form of strain due to moving loads and a bridge structure response that was reduced by approximately 50% from the deflection force on the steel frame reference bridge if given a moving load. Choosing a bridge that has the lowest settlement. The review point is determined for the comparison of deflection at point object 7 and joint object U3. The Type E cable-stayed bridge has the lowest results in percentage, about 46.68% for a speed of 40 km/h, 48.60% for a vehicle speed of 50 km/h and 49.91% for a vehicle speed of 60 km/h, indicating that this bridge has the best analysis performance among the cable-stayed bridges analyzed.